2019
DOI: 10.21037/jtd.2019.10.41
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support in chronic obstructive pulmonary disease (COPD): an evidence update

Abstract: Chronic obstructive pulmonary disease (COPD) primarily affects the lungs but due to the accompanying chronic systematic inflammation and the symptoms associated with the disease there are many extrapulmonary effects which include complex physical and metabolic adaptations. These changes have been associated with reduced exercise capacity, increased nutritional requirements, altered metabolic processes and compromised nutritional intake. As a result, nutritional depletion in COPD is multi-faceted and can involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 48 publications
0
46
0
2
Order By: Relevance
“…However, it also should pay attention to identify the specific goals of nutritional intervention (energy imbalance, sarcopenia, cachexia, frailty) in practice. 31 Some researchers have suggested that medical nutrition therapy can provide sufficient levels of protein, the amino acid leucine, vitamin D, and polyunsaturated fatty acids, which may be beneficial for the treatment of sarcopenia and functional decline. 32 Identification of frailty or pre-frailty in patients with COPD as early as possible and formulation and evaluation of tailored intervention programs may yield greater patient benefits.…”
Section: Discussionmentioning
confidence: 99%
“…However, it also should pay attention to identify the specific goals of nutritional intervention (energy imbalance, sarcopenia, cachexia, frailty) in practice. 31 Some researchers have suggested that medical nutrition therapy can provide sufficient levels of protein, the amino acid leucine, vitamin D, and polyunsaturated fatty acids, which may be beneficial for the treatment of sarcopenia and functional decline. 32 Identification of frailty or pre-frailty in patients with COPD as early as possible and formulation and evaluation of tailored intervention programs may yield greater patient benefits.…”
Section: Discussionmentioning
confidence: 99%
“…138 Polyunsaturated fatty-acids (PUFA's), more specifically omega-3 PUFA's have been implicated to modulate (systemic) inflammatory processes, to boost muscle mitochondrial metabolism and to positively affect protein synthesis and exercise capacity. 5,54,[138][139][140][141] Positive effects of PUFA supplementation on exercise capacity in COPD has indeed been demonstrated, 142 adding to the rationale for supplementation of PUFA's next to sufficient protein intake to prevent or treat sarcopenia in COPD, but further evidence from clinical trials is needed. 143 Vitamin D deficiency is common in COPD patients, especially in elderly patients.…”
Section: Nutritionmentioning
confidence: 99%
“…146 Studies are diverse in their exact strategies, but a combination of exercise training with additional supplementation of different combinations of dietary protein (whey), PUFA's and vitamin D are reported to maintain or improve FFM in both primary sarcopenia and sarcopenic COPD patients. 56,141,147,148 Pharmacology A combination of exercise therapy and nutritional interventions might not always be feasible in COPD patients with severe respiratory impairment or sarcopenia.…”
Section: Nutritionmentioning
confidence: 99%
“…In turn, this is due to an imbalance between protein synthesis and breakdown. Malnutrition and weight loss are common among people with COPD and certain metabolic characteristics, such as a depleted fat mass and fat-free mass, can further impact on the loss of lung function capacity [ 13 , 60 ]. These features may be observed in stable COPD irrespectively of the degree of airflow limitation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%